An assessment of capital expenditure, required to establish a steel distribution business, as a barrier to entry into the steel distribution industry - Gqoboka, Lithalethu (Graduate School of Business (GSB), 2018)
The South African steel industry plays a vital role in the economy of the country. It is seen to be a major source of employment for the South African people, and key to sustainable economic development for the country. In recent years however, the South African steel industry has been faced with a number of challenges resulting in the closure of some steel companies and consequently the loss of many jobs. It is posited that small and medium enterprises (SMME’s) can minimise these negative effects, balance out the job losses and keep the industry sustainable. However, the barriers to entry in the steel industry, and especially access to finance capital, require policy interventions to assist entrepreneurs to enter into the industry. This paper explores the barriers to entry for new entrants in the industry, with particular focus on capital expenditure as the main barrier to entry and seeks to understand what policy interventions would be beneficial in promoting new entrants into the steel industry value chain. Qualitative research was undertaken to gather data from senior personnel within various steel companies. A convenience sample of eleven participants were selected to participate in semistructured interviews. Transcripts of the interviews were used to conduct an analysis of findings. The research found that there is scope for new players in the steel industry value chain but that it is a highly competitive industry with many players currently. New entrants would need to focus on innovation or a niche area of specialisation, in order to compete effectively. In addition, having additional players would benefit the industry and contribute positively to economic development for the country. The largest challenge for new entrants is access is capital as financial institutions are risk adverse towards to the steel industry. However, there are various means by which small players can minimise the necessary capital outlay for a startup business. Policy interventions can also go a long way in encouraging additional entrants to the industry and further developing the economy.